Preferential investment liberalization under bilateral investment treaties: How to ensure compliance with WTO law? - Robert Basedow (Columbia University, Columbia Center on Sustainable Investment (CCSI), 2015)
Numerous modern bilateral investment treaties seek to liberalize bilateral investment flows on a preferential basis. This Perspective argues that such liberalization commitments are likely to be multilateralized under the General Agreement on Trade in Services. It discusses how policy-makers may avoid the multilateralization of such bilateral liberalization commitments.
Keywords: 330